A Differentiated strategy for IICA in the Caribbean (2017-2021 : proposal for discussion - Otero, Manuel (2017)
Addresses relevant themes of climate change (both pre- and post-extreme weather events), food and nutrition security; and the attendant imperatives for the modernisation, reinvigoration and restructuring of the agri-food systems.